Supercritical CO2 deposition and foaming process for fabrication of biopolyester–ZnO bone scaffolds. Issue 7 (16th October 2017) - Ivanovic, Jasna; Rezwan, Kurosch; Kroll, Stephen
ABSTRACT: Subsequent supercritical CO2 ‐assisted deposition and foaming process followed by in situ synthesis was used to fabricate functional polylactide (PLA) and polylactide–poly(ɛ‐caprolactone) (PLA–PCL) bone scaffolds. Deposition of zinc bis(2‐thenoyltrifluoroacetonate) as a ZnO precursor onto biopolyester substrates (30 MPa; 110 °C) was followed by fast depressurization to create cellular structure. Contact time was optimized regarding the deposition yield (2 h), while PCL content in PLA was varied (1–10 wt %). Scaffolds impregnated with the precursor were treated with hydrazine alcoholic solution to obtain biopolyester–ZnO composites. Precursor synthesis and deposition onto the scaffolds was confirmed by Fourier‐transform infrared. Processed scaffolds had micron‐sized pores ( d 50 ∼ 20 μm). High open porosity (69–77%) and compressive strength values (2.8–8.3 MPa) corresponded to those reported for trabecular bone. PLA blending with PCL positively affected precursor deposition, crystallization rate, and compressive strength of the scaffolds. It also improved PLA surface roughness and wettability which are relevant for cell adhesion. ZnO improved compressive strength of the PLA scaffolds without significant effect on thermal stability. Analysis of structural, thermal, and mechanical properties of biopolyester–ZnO scaffolds testified a great potential of the obtained platforms as bone scaffolds. Proposed processing route is straightforward and ecofriendly, fast, easy to control, and suitable for processing of thermosensitive polymers. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2018, 135, 45824. Abstract :